Pelanggaran Privasi Dalam Program Realita Investigasi Polisi di Indonesia: Ancaman, Kebijakan, Dan Kebutuhan Pembaruan - Ditia Saputra, Dandi; Ayu Pramesty , Ligar; Farah Munifah, Nabila (CIC Lembaga Riset dan Konsultan Sosial, 2023)
The high popularity of police investigation reality programs in content broadcast on television and online media (YouTube) increases the possibility of doxing. Several laws, especially Law no. 19 of 2016, have provisions regarding the protection of personal life. However, until now, there has been no regulation that clearly regulates the authority for the participation of television stations in the process of finding investigative facts. This paper aims to find a legal basis for privacy violations against police investigation reality program coverage and to formulate a more comprehensive privacy protection instrument. This research is a normative research with a statutory approach. The research shows that there is a debate between public interest and privacy protection in the coverage of police investigative reality programs, as well as violations of laws and ethical codes committed by the Republic of Indonesia police and private television stations. The presence of the concept of protecting privacy for the public, especially suspects, is expected to be the main value base considered in every coverage of the police investigative reality program. Tingginya popularitas program realita investigasi polisi dalam konten penayangan di media penyiaran televisi dan media online (YouTube) meningkatkan kemungkinan doxing. Beberapa Undang-Undang terutama Undang-Undang No. 19 Tahun 2016 memiliki ketentuan mengenai perlindungan kehidupan pribadi, walaupun demikian sampai saat ini belum ada regulasi yang dengan jelas mengatur mengenai otoritas keikutsertaan stasiun televisi dalam proses pencarian fakta investigasi. Tulisan ini bertujuan mencari dasar hukum pelanggaran privasi terhadap peliputan program realita investigasi polisi dan merumuskan instrumen perlindungan privasi yang lebih komperhensif. Penelitian ini merupakan penelitian normatif dengan pendekatan perundang-undangan. Penelitian menunjukkan adanya perdebatan antara kepentingan publik dan perlindungan privasi dalam peliputan program realita investigasi polisi serta adanya pelanggaran hukum serta kode etik yang dilakukan oleh kepolisian Republik Indonesia dan stasiun televisi swasta. Hadirnya konsep perlindungan privasi bagi masyarakat khusunya tersangka diharapkan menjadi basis nilai utama yang diperhatikan dalam setiap peliputan program realita investigasi kepolisian.